Pengaruh Dukungan Universitas dan Keterampilan Kepemimpinan Terhadap Intensi Berwirausaha - Nurlatifah, Nurlatifah; Kurjono, Kurjono; Setiawan, Yana (Universitas Pendidikan Indonesia, 2021)
Various efforts to increase the low entrepreneurial intention of college students. Therefore, this study aims to find out how the effect of university support and leadership skill on Entrepreneurship Intentions.Â The grand theory of this research is the Planned Behavior theory from Ajzen.Â The research method used is the Explanatory Survey Method. Research samples were taken from UPI's student population from 13 sections, faculty and regional campuses. The populations are 19,919 students with sample sizes using Isaac Michael formula that obtained 366 respondents. Data collection is using numerical-scale-questionnaires. All questionnaires are tested for validity and reliability. Data analysis techniques use regression analysis in order to find the effect of university support variable and leadership skill on entrepreneurship intentions. The results showed university support and leadership skill had a positive effect on entrepreneurial intention. It is recommended to improve the indicator of the university support variable on business development support, it can be improved through coaching student entrepreneur candidates through business incubators. An indicator that needs to be improved from the leading skill variable is human skill through increasing entrepreneurial activities of college students.